MERANCANG PEMBELAJARAN BERDIFERENSIASI BERDASARKAN GAYA BELAJAR PADA PELAJARAN IPA MATERI EKOSISTEM DI SEKOLAH DASAR - Satuti, Luxmita Anna (MAGISTRA: Media Pengembangan Ilmu Pendidikan Dasar dan Keislaman, 2024)
This study aims to explore the design of differentiated learning content that accommodates the sensorial learning style of Grade 5 students. The research uses a qualitative approach, involving interviews and questionnaires with teachers at SD Negeri Inpres Malompo. The results show that teachers have implemented various content types, including texts, videos, student activity sheets, and diagrams, to cater to students' different learning styles. Factors that contribute to the implementation of sensorial learning style-based differentiated content include teachers' educational background, teaching experience, and external factors such as facilities, infrastructure, and time. The study concludes that understanding students' learning styles is crucial in designing effective differentiated learning content, and that teachers play a vital role in creating an inclusive learning environment that caters to individual students' needs. The findings of this study can be used to develop more effective and inclusive learning strategies, and to assist teachers in designing learning content that suits students' learning styles.